Steel slag and recycled concrete aggregates: replacing quarries to supply sustainable materials for the asphalt paving industry - Loureiro, Carlos Daniel Aleixo; Moura, Caroline Fernandes Nunes; Rodrigues, Mafalda; Martinho, Fernando C. G.; Silva, Hugo M. R. D.; Oliveira, Joel R. M. (Sustainability, 2022)
Various researchers are developing efforts to integrate waste and by-products as alternative materials in road construction and maintenance, reducing environmental impacts and promoting a circular economy. Among the alternative materials that several authors have studied regarding their use as partial or total substitutes for natural aggregates in the asphalt paving industry, the steel slag aggregate (SSA) and recycled concrete aggregate (RCA) from construction demolition waste (CDW) stand out. This paper reviews and discusses the characteristics and performance of these materials when used as aggregates in asphalt mixtures. Based on the various studies analyzed, it was possible to conclude that incorporating SSA or RCA in asphalt mixtures for road pavements has functional, mechanical, and environmental advantages. However, it is essential to consider some possible drawbacks of these aggregates that are discussed in this paper, to define the acceptable uses of SSA and RCA as sustainable feedstocks for road paving works. This research was funded by the "Environment, Climate Change and Low Carbon Economy Programme-Environment Programme" (EEA financial mechanism 2014-2021) through the Funding Mechanism Commission established by Iceland, Liechtenstein, Norway, and Portugal, under the scope of project CirMat-CIRcular aggregates for sustainable road and building MATerials. This study was also supported by Fundacao para a Ciencia e a Tecnologia through the Ph.D. grants number 2021.06428.BD and 2021.08004.BD.